A study about different findings of PET-CT between neoadjuvant and non-neoadjuvant therapy: SUVmax is not a reliable predictor of lymphatic involvement after neoadjuvant therapy for esophageal cancer - Park, Jae Kil; Kim, Jae Jun; Moon, Seok Whan (Journal of Thoracic Disease, 2016)
Background: No definitive findings or established guidelines have been published for the evaluation of esophageal tumors (tumor) and regional lymph nodes (LN) using positron emission tomography computed tomography (PET-CT) in patients with esophageal cancer. In addition, it remains unclear whether PET-CT findings vary between neoadjuvant (NT) and non-neoadjuvant (non-NT) therapy cases. Therefore, preoperative evaluation using PET-CT might provide unreliable information and influence the management plan for esophageal cancer. The purpose of the present study is to clarify the different findings of PET-CT between NT and non-NT in surgical esophageal cancer cases and to predict LN metastasis. Methods: We retrospectively reviewed the medical records of 192 consecutive cases that met this study’s inclusion criteria from January 2009 to December 2014. All patients underwent curative and complete esophagectomy for intra-thoracic esophageal cancer at the department of thoracic and cardiovascular surgery in a single tertiary Korean hospital. We compiled and analyzed maximum standard uptake values (SUVmax) of tumor and LNs with other clinical information (chronic lung disease, history of previous other primary cancer, sex, pathological findings, NT, and other clinical data). Results: (I) In NT, a positive correlation between T stage and SUVmax was found (tumor SUVmax P